2014
DOI: 10.2967/jnumed.114.142927
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of 18F-FDG Accumulation in Colorectal Cancer Cells with Mutated KRAS

Abstract: KRAS gene mutations occur in approximately 40% of colorectal cancers (CRCs) and are associated with resistance to anti-epidermal growth factor receptor antibody therapy. We previously demonstrated that 18 F-FDG accumulation in PET was significantly higher in CRCs with mutated KRAS than in those with wild-type KRAS in a clinical setting. Here, we investigated the mechanisms by which mutated KRAS increased 18 F-FDG accumulation. Methods: Using paired isogenic human CRC cell lines that differ only in the mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 23 publications
3
55
0
Order By: Relevance
“…Moreover, this result was confirmed in cultured cells and xenograft models of thyroid and colon cancer, respectively, resulting in accumulation of 18F-FDG. [33,34] Consistent with these results, the correlation between Kras mutation status and Glut1 expression was confirmed in G22Cre;Apc flox/ flox ;Kras G12D mice with a potential MSI phenotype based on our previous observation in G22Cre;Apc flox/flox ;KrasWT mice [28]. Thus, the G22Cre;Apc flox/flox ;Kras G12D mouse model may recapitulate the human KRAS mutated colorectal cancer with MSI phonotype.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, this result was confirmed in cultured cells and xenograft models of thyroid and colon cancer, respectively, resulting in accumulation of 18F-FDG. [33,34] Consistent with these results, the correlation between Kras mutation status and Glut1 expression was confirmed in G22Cre;Apc flox/ flox ;Kras G12D mice with a potential MSI phenotype based on our previous observation in G22Cre;Apc flox/flox ;KrasWT mice [28]. Thus, the G22Cre;Apc flox/flox ;Kras G12D mouse model may recapitulate the human KRAS mutated colorectal cancer with MSI phonotype.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we investigated a possible association between KRAS status and HIF-1a expression by immunohistochemical analysis and found that HIF-1a did not correlate with KRAS status in metastatic CRC (data not shown). Our previous studies on primary CRC showed a significant correlation between HIF-1a and KRAS status (10). One possible reason for this discrepancy may be the difference in tumor size (primary CRC, 47.9 6 20 vs. metastatic CRC, 20.9 6 14.2 mm; P , 0.01).…”
Section: Discussionmentioning
confidence: 90%
“…When CRC cells were treated under hypoxic conditions, mutated KRAS enhanced the translation of HIF-1a through the phosphoinositide 3-kinase pathway (26). We recently reported that CRC cells with mutated KRAS increased 18 F-FDG accumulation by upregulating GLUT1 and at least partially by upregulating HIF-1a induction under hypoxic conditions (10). In this study, we investigated a possible association between KRAS status and HIF-1a expression by immunohistochemical analysis and found that HIF-1a did not correlate with KRAS status in metastatic CRC (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thei nvestigation of molecular uptake inside cells is valuable for the understanding of physiologic status (1,2), for the interpretation of molecular imaging results (3,4), and for the development of imaging agents and pharmaceuticals (5). The cellular uptake of a molecule is usually assessed by measuring labeling signals such as radioactivity (2,6), optical signal (7), or magnetic signal (8).…”
mentioning
confidence: 99%